Avian influenza overview August – November2019. (20th December 2019) - ,; ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Kuiken, Thijs; Smietanka, Krzysztof; Staubach, Christoph; Guajardo, Muñoz; Baldinelli, Francesca
Abstract : Between 16 August and 15 November 2019, one low pathogenic avian influenza (LPAI) A(H5) outbreak in poultry in France was reported in Europe. Genetic characterisation reveals that the virusclusterswith Eurasian LPAI viruses. No highly pathogenic avian influenza (HPAI) outbreaks in birds were notified in Europe in the relevant period for this report. HPAI A(H5N6) viruswas identified in chickens in Nigeria, this isthe first report of HPAI A(H5N6) from the African continent.FewerHPAI outbreaks in Asia and Africa were reported during the time period for this report compared with the previous reporting period. Apart from the long‐term epidemic of HPAI A(H5N2)in Taiwan, only six HPAI outbreakswere reported in domestic birds from Nepal, South Africa and Taiwan. Furthermore, no HPAI detections fromwild birds were reported worldwide in the relevant time period forthis report.Even if the risk of incursion of HPAI from wild birds into poultryestablishments in Europe is currently assessed as low, it is important to maintain passive surveillance activities. The focus should be on wild bird species that are in the revised list of target species in order to detect any incursion of HPAI virus early and initiate a warning.Despite the decrease in the number of avian influenza outbreaks over recent months, it is important to maintain a high alert level andhigh standard of biosecurity onpoultry establishments.In Europe, no human infections due toHPAI viruses detected in wild bird or poultry outbreaks, have been reported. The risk of zoonotic transmission to the general public in Europe is considered to be very low.